Dinamika Kerja Emosional: Konflik Antara Emosi yang dirasakan dan ditampilkan pada Sektor Pelayanan - Kirani Deniar; Mohammad Daffa Nugraha; Putri Amalia; Ulfah Albirru Roihan; Gurawan Dayona Ismail; Asep Rinda Kramawijaya (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Emotional labor is a key demand in service sector jobs, requiring employees to manage and display emotions according to organizational expectations. The mismatch between felt and displayed emotions, or emotional dissonance, can lead to work stress, emotional exhaustion, decreased job satisfaction, and even burnout. This study aims to describe the dynamics of emotional labor, identify the emotion regulation strategies used by workers, and explain the role of psychological flexibility in mitigating the negative impacts of emotional labor. The study used a qualitative descriptive method with a literature review approach through analysis of various journals, books, and relevant previous research using content analysis techniques. The results indicate that workers often experience emotional dissonance due to the demands of display rules. Continuous use of surface acting increases the risk of emotional exhaustion, while deep acting and psychological flexibility promote more adaptive emotional regulation, improve psychological well-being, and maintain service quality.